Progress in epigenetic research of breast cancer: a bibliometric analysis since the 2000s - Yang, Hua; Fang, Yu; Wang, Haijuan; Lu, Ting; Chen, Qihua; Liu, Hui (Frontiers in Oncology, 2025)
BackgroundBreast cancer continues to be a leading cause of cancer-related deaths among women worldwide. Despite advancements in diagnostics and therapies, challenges such as metastasis, recurrence, and resistance remain prevalent. Recently, research has shifted from traditional genomic analyses to the study of epigenetic regulation, which includes DNA methylation, histone modifications, and non-coding RNAs. Given the rapid expansion of literature in this field, a systematic overview of its evolution and emerging trends is necessary.MethodsWe performed a comprehensive bibliometric analysis of 5,271 articles on breast cancer epigenetics, sourced from the Web of Science Core Collection, covering the years 2000 to 2024. Utilizing tools like CiteSpace and VOSviewer, with support from RStudio, Pajek, and HisCite, we analyzed co-citation networks, keyword co-occurrence, and burst detection. This analysis included visualizations of collaboration among authors, institutions, and countries. Metrics such as modularity, silhouette scores, and betweenness centrality were used to ensure analytical rigor and to identify thematic evolution and emerging research frontiers.ResultsFrom 2000 to 2018, the number of annual publications increased steadily, with citation peaks occurring in 2021. The United States led in research output and influence, followed by China. Leading institutions included Johns Hopkins University and the University of Texas MD Anderson Cancer Center. Keyword and co-citation analyses revealed four research phases: (1) early studies focused on promoter hypermethylation of tumor suppressor genes like RASSF1A; (2) an in-depth investigation of molecular mechanisms, including epithelial-mesenchymal transition and chromatin remodeling; (3) translational research involving HDAC inhibitors and DNA methylation biomarkers; and (4) recent advancements in multi-omics integration, synthetic lethality, and the study of epigenetics in the tumor microenvironment. Emerging research directions include the targeted removal of epigenetic memory, metabolism-epigenetics networks, and single-cell epigenomic profiling.ConclusionThis bibliometric study outlines the trajectory of research in breast cancer epigenetics, highlighting its evolution from basic methylation studies to advanced therapeutic exploration. Future research should focus on targeting epigenetic memory to combat drug resistance and recurrence, developing synthetic lethality strategies, and employing single-cell technologies for dynamic epigenetic mapping. These findings provide a strategic roadmap for researchers and policymakers navigating the evolving landscape of breast cancer epigenetics.